Past and future behavior of the valley glaciers in the Italian Alps - Serandrei-Barbero, Rossana; Donnici, Sandra; Zecchetto, Stefano (Frontiers in Earth Science, 2022)
The behavior of the valley glaciers of the Italian Alps as a result of the climate changes expected for the 21st century has been investigated. From 1980 to 2017 the average length reduction of these glaciers has been 13% and their average areal reduction was around 22%. The mean climate sensitivity of the considered glaciers is 410 mK-1 and their mean observed shortening was about 500 m for a temperature increase of 1.4 °C. To quantify the valley glacier life expectancy, a model estimating their length variations from the air temperature variations of the EuroCordex climatological projections of six different models under the RCP4.5 and RCP8.5 scenarios has been used. The ensemble mean temperatures in the Italian Alps region under these scenarios indicate increases in the temperature of ~2°C and ~4°C from 2018 to 2100 respectively. The glacier projections are mean values, taking into account the errors due to the model (6-16%) and the different climatological forcings (up to 20-30%). Under the RCP4.5 scenario, the glacier model projections show a constant retreat until the 2080s, with a weakening around 2090s and the 87% of glaciers surviving. Under the RCP8.5 scenario, only three glaciers could reach the end of the century, while 80% of them will probably disappear between the 2060s and the 2080s.